Being smart about writing SMART objectives - Bjerke, May Britt; Renger, Ralph (Evaluation and program planning, 2017)
•The SMART method is a mainstream method for developing program objectives.•When baseline data is missing users cannot apply all SMART criteria simultaneously.•Future SMART objective guidance should delineate between different contexts. This article challenges the conventional wisdom in mainstream evaluation regarding the process for developing specific, measurable, attainable, relevant, and time-bound (SMART) objectives. The article notes several advantages of mainstreaming the SMART method including program capacity building and being able to independently monitor progress toward process and outcome objectives. It is argued the one size fits all approach for writing SMART objectives is misleading. The context in which the evaluation is conducted is a key deciding factor in how and when the SMART criteria should be applied. Without an appreciation of the evaluation context, mainstream users may be developing objectives that are far from smart. A case example is presented demonstrating a situation where a stepwise, rather than simultaneous application of the SMART criteria was necessary. Learning from this case, recommendations are forwarded for adjusting how SMART criteria should be presented in mainstream evaluation manuals/guides.